THE EFFECT OF BRAND IMAGE AND BRAND TRUST ON CUSTOMER LOYALTY IN THE CAMEL BRAND ACTIVE SHOES AT SOGO TUNJUNGAN PLAZA IV SURABAYA - Diana Deta Sari; Sengguruh Nilowardono; Ani Wulandari (Journal of World Conference (JWC), 2019)
ABSTRACT This study aims to analyze the effect of brand image and brand trust on customer loyalty in the Camel brand Active Shoes at Sogo Tunjungan Plaza IV Surabaya. This research is quantitative research. Population and sample based on questionnaire distribution to consumers who have made a repeat purchase, have had it before, and visited the Camel brand Active Shoes product site at Sogo Tunjungan Plaza IV Surabaya many as 160 respondents. Furthermore, there are three variables used in this study, namely : brand image (X1), brand trust (X2), and customer loyalty (Y). The results show that the variable brand image (X1) has a significant effect partially on customer loyalty, while the variable brand trust (X2) has a significant effect partially on customer loyalty. Research the results variables brand image and brand trust have a significant effect simultaneously on customer loyalty in the Camel brand Active Shoes at Sogo Tunjungan Plaza IV Surabaya. Data collection techniques using interviews, observation and questionnaires. Analysis of the data used is validity test, reliability test, classic assumption test, multiple linear analysis test and hypothesis test.